ADVANTAGE OF DAIRY FARMING THROUGH SELF HELP GROUPS AND JOINT LIABILITY GROUPS (Indian Journal of Animal Production and Management, 2013)
A study was carried out in the districts of Barpeta and Kamrup in the state of Assam where the Self Help Group and Joint Liability Group on dairying were more concentrated. A total of 100 respondents were interviewed to study the advantages of SHG and JLG in regards to quality of milk production, marketing, veterinary services etc. The data analysis revealed that 99% of the SHG members falling in medium to high group of advantages and in case of JLG it was 100%. Quality production of milk, fodder cultivation and record keeping excelled the dairying atmosphere in case of SHG whereas JLGs were more advantageous with additional attributes like marketing, quality production of milk with subsequent order of preference in veterinary service, line benefit and quality life. About 64% of the members of SHG and 96% of the members of JLG had the privilege of having credit linkage from different financial institutions including the microfinance institutions.
Keywords: Dairy farming; Joint liability Group (JLG); Self Help Group (SHG)